Being More: coherence between life and Paulo Freire’s concept (Práxis Educativa, 2021)
In this text, the coherence between the theoretical construction of the concept of Being More with the actions taken throughout Freire’s life, which may justify the repercussion of his work is discussed. The study started from the analysis of 12 interviews with Paulo Freire from 1992 to 1997, available at Paulo Freire Collection. After the analysis, it was identified nine characteristics of Being More, namely: self-awareness; awareness of the world; hope; dealing with difference – learning who I am; being and humility; cultural identity; being political – non-neutrality; and dream. It is noted that there is a coherence between the theorization of the Being More concept and the historical, unfinished, limited being that never betrayed his/her dreams. Freire has always denounced the exploitative and unjust society and proposed the liberating education that announces a more democratic and inclusive society. An education in which Being More is the goal of all students and educators.Keywords: Liberating education. Being more. Paulo Freire.